Evaluation of in vitro properties of predicted kinases that phosphorylate serine residues within nuclear localization signal 1 of high mobility group box 1. (25th May 2014) - Taira, Junichi; Higashimoto, Yuichiro
<x xml:space="preserve">Abstract</x> Phosphorylation of high mobility group box 1 (HMGB1) is involved in the subcellular translocation of this protein and its subsequent secretion. Two nuclear localization signals (NLSs), NLS1 and NLS2, in this protein regulate its nucleocytoplasmic relocation, and phosphorylation of both NLSs strongly promotes HMGB1 mobilization. However, the phosphorylation properties of serine residues in NLS1 and the kinases involved are not well known. In the present study, we predicted kinases that phosphorylate serine residues in NLS1 and performed an in vitro kinase assay utilizing NLS1‐derived phosphopeptides. Among the predicted kinases, protein kinase C phosphorylated Ser46 of HMGB1‐derived peptides, and a mutagenesis experiment confirmed that phosphorylation at this site could induce the translocation of the N‐terminal region of NLS1‐containing HMGB1 into the cytosol. Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.